Will the integration of renewable energy enable sustainable transition of Indian electricity system?. (August 2018) - Sharma, Tarun; Balachandra, P.
Abstract: Electricity systems worldwide are transitioning from conventional carbon intensive firm power generating systems to intermittent and variable renewable energy dominated low carbon systems. Although the dimensions of transition vary from one electricity system to another, there is concurrence in terms of need for and the subsequent issues related to renewable energy integration. In this study, we attempt to verify whether these transitions lead to a sustainable electricity system as measured through three dimensions – economic, social and environmental. This is performed by adopting an integrated framework, which connects the indicator based multi-hierarchical and multidimensional macro model of electricity system sustainability assessment with the bottom up optimization model of generation expansion planning and generation scheduling. We explore multiple scenarios and characterize Indian electricity system on select indicators under three sustainability dimensions. We aggregate this annual characterization to compute National Electricity System Sustainability Index (NESSI). NESSI value for base year is 0.377 (2013) and within the select scenarios, it varies from 0.481 to 0.510 in 2031. These variations in extent of sustainability are influenced by underlying technology choices. Thus, Indian electricity system is transitioning towards a more sustainable state. We provide additional insights on how the important questions concerning generation technology pathways for electricity system sustainability transition can be queried and the underlying choices this process involves. Highlights: Sustainability assessment of transitioning Indian electricity system. Model based feasibility and sustainability assessment of Indian electricity scenarios. Renewable energy integration enables sustainability transition of electricity system. Cost of sustainability transition is Rs. 0.83/kWh which results in a saving of 0.27 kgCO2 /kWh.